2007
DOI: 10.1055/s-2007-985816
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prevalence of the Metabolic Syndrome by WHO, AHA/NHLBI, and IDF Definitions in a German Population with Type 2 Diabetes: The Diabetes in Germany (DIG) Study

Abstract: major cardiovascular event < 3 months before entry, NYHA-IV, macroproteinuria, and cancer < 5 years before entry. The components of MetS were measured following a standard protocol for anthropometric and laboratory control. The average diabetes duration was 8.4 years and HbA (1C) 7.0%. The prevalence of MetS by WHO criteria was 26.1%, by AHA/NHLBI 79.3%, and by IDF 82.6%. The degree of agreement (kappa statistic) was kappa = 0.69 between AHA/NHLBI and IDF definitions, but only 0.12 for WHO VS. IDF, and 0.17 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 3 publications
1
36
2
1
Order By: Relevance
“…On the other hand, several reports have shown that hypertension is very prevalent among Europeans with DM and the highest and the lowest rates were 95% and 29.3%, respectively [27][28][29]. In USA, 70.9% was the highest prevalence of hypertension among type 2 DM patients and the lowest prevalence reported was 66.9% [30].…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, several reports have shown that hypertension is very prevalent among Europeans with DM and the highest and the lowest rates were 95% and 29.3%, respectively [27][28][29]. In USA, 70.9% was the highest prevalence of hypertension among type 2 DM patients and the lowest prevalence reported was 66.9% [30].…”
Section: Discussionmentioning
confidence: 93%
“…The clustering of risk factors for CVD is seen as a universal phenomenon among people with type 2 diabetes [10][11][12][13][14]. MS is also a stronger and independent predictor for heart disease in type 2 diabetic patients [10,14].…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence to suggest that modification of these factors results in a substantial decrease and delay in the development of heart diseases [8,9]. Metabolic syndrome (MS) is a clustering of such risk factors and its prevalence is found to be nearly 60% to 80% among diabetic patients in different parts of the world [10][11][12][13]. Although, MS is known as a significant and independent predictor of cardiovascular disease, its presence among persons with type 2 diabetes raises this risk to the greatest [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The major features of the 32 These definitions are having many similarities, however, they differ in some of their components and cut-offs. In the general population, prevalence of the MetS vary according to the definition used 33 and its prevalence increases with age. 34,35 The prevalence of MetS in patients with RA in various published studies is shown in Table 1.…”
Section: Metabolic Syndromementioning
confidence: 99%